Knorr-Rabe partial reduction of pyrroles: Application to the synthesis of indolizidine alkaloids - Gourlay, Brendon S (Beilstein-Institut, 2008)
BACKGROUND: The Birch reduction of electron rich pyrroles does not occur readily. However, dissolving metal reduction with zinc under acidic conditions gives 3-pyrrolines (2,5-dihydropyrroles) in reasonable yield. This dissolving metal reduction was first reported by Knorr and Rabe in 1901 but since then has only been reported for the reduction of electron rich pyrroles. RESULTS: The partial reduction of bicyclic α-ketopyrrole derivatives has been performed under dissolving metal conditions with zinc and hydrochloric acid to give excellent yields of hexahydroindolizidines. This reduction method has been utilised for the diastereoselective synthesis of 5-alkylindolizidines and the stereoselectivity obtained is opposite to that of catalytic hydrogenation. CONCLUSION: An efficient stereoselective synthesis of indolizidine alkaloids has been developed from α-ketopyrrole intermediates using a modified version of Knorr and Rabe's pyrrole reduction.